Ons dak nie ... ons phola hierso: politics, protest and proletarians in Sophiatown, 1930-1955 - Lebelo, Steve (My University, 1991)
Existing interpretations of the failure of resistance to the forced removal of Sophiatown in 1955 have been grossly inadequate. The emphasis has been on the political programmes and strategies of organised politics which articulated the interests of property owners. Sophiatown's marginalised and underprivileged classes - tenants and sub-tenants - have been largely ignored. This study focuses exclusively on tenants and sub-tenants in Sophiatown. It explores their urban experiences as shaped by the patterns of migration that chareterised them; the nature and function of the rural ties that they evolved in the city and forms of accommodation that they desired and procured. Further the study attempts to analyse elements of political apathy and acquiescence among the largest proportion of Sophiatown's population. Sophiatown and Martindale (henceforth Sophiatown) were inhabited by a community that did not share similar characteristics of urban culture with Newclare and Western Native Township (WNT). It is argued in this study that, theoretically, Sophiatown developed in sharp contrast with the other two townships. The violent unrest of 1949 and 1950 was a result of the conflict of interest between the local state and the communities in Newclare and WNT. It was a conflict in which the Sophiatown community was relatively uninvolved. This paper is divided into four sections. In section I, Sophiatown's early history is examined. Initially, the township was inhabited by White home-owners. By 1912 Africans, most of whom were living in family circumstances and who were relatively affluent were obtaining properties in Sophiatown. However, for three decades population growth remained relatively insignificant. Section II focuses on the growth of tenants and sub-tenants in Sophiatown against the backdrop of slum clearance in the center of Johannesburg. In section III the paper examines political protest in the Western Areas of Johannesburg and how Sophiatown’s tenant classes were affected by and responded to conflicts between the "agents of external authority" - the local state - and the community in the region. The concluding section focuses on the implications of the Western Areas Scheme on Sophiatown's tenants and sub-tenants. It is argued that conflicts with landlords and promises of more living space in Meadowlands were not the overriding concerns of Sophiatown's tenant classes. The threat of forced removals in 1950 would have resolved the crisis that affected tenant classes' reproductive capacity created by changing material conditions in the rural districts. However, at this stage such a hypothesis is only speculative as evidence remains inconclusive.
African Studies Seminar series. Paper presented March 1991
Keywords: Blacks. Relocation. South Africa